Gettysburg religion: refinement, diversity, and race in the antebellum and Civil War border north - Longenecker, Stephen L. (The North's Civil War, 2014)
"Brings to life the religious history of a small and famous town and the surrounding area, the Border North. The theme is that Gettysburg religion reveals much about larger American society, often something unexpected and indicative of the Border North's advanced modernity"--